Decreases in Dorsal Cervical Spinal Cord White Matter Tract Integrity Are Associated with Elevated Levels of Serum MicroRNA Biomarkers in NCAA Division I Collegiate Football Players - Linda Papa; Brian Johnson; Alexa E. Walter; James R. Wilkes; Barbara Knollmann-Ritschel; Manish Bhomia; Semyon M. Slobounov (Neurotrauma Reports, 2021)
This prospective, controlled, observational cohort study assessed the performance of a novel panel of serum microRNA (miRNA) biomarkers relative to findings on cervical spinal cord magnetic resonance imaging (MRI) in collegiate football players. There were 44 participants included in the study: 30 non-athlete control subjects and 14 male collegiate football athletes participating in a Division I Football Bowl Subdivision of the National Collegiate Athletic Association. Diffuse tensor MRI and blood samples were acquired within the week before the athletic season began and within the week after the last game of the season. All miRNAs were significantly higher in athletes regardless of their fractional anisotropy (FA) values (p?<?0.001), even those considered to be in the ?normal? range of FA for white and gray matter integrity in the cervical spinal cord. miRNA biomarkers were most significantly correlated with FA of the white matter (WM) tracts of the dorsal (posterior) spinal cord; particularly, the fasciculus gracilis, fasciculus cuneatus, lateral corticospinal tract, rubrospinal tract, lateral reticulospinal tract, spinal lemniscus, and spinothalamic and -reticular tracts. Areas under the curve for miRNA biomarkers predicting lower FA of WM dorsal (posterior) cervical spinal tracts, therefore lower white matter integrity (connectivity), were miR-505*?=?0.75 (0.54?0.96), miR-30d?=?0.74 (0.52?0.95), and miR-92a?=?0.75 (0.53?0.98). Should these findings be replicated in a larger cohort of athletes, these markers could potentially serve as measures of neuroimaging abnormalities in athletes at risk for concussion and subconcussive injuries to the cervical spinal cord.